2020
DOI: 10.1038/s41598-020-70930-1
|View full text |Cite
|
Sign up to set email alerts
|

Promotional effect of magnesium oxide for a stable nickel-based catalyst in dry reforming of methane

Abstract: The generation of synthesis gas (hydrogen and carbon monoxide mixture) from two global warming gases of carbon dioxide and methane via dry reforming is environmentally crucial and for the chemical industry as well. Herein, magnesium-promoted NiO supported on mesoporous zirconia, 5Ni/xMg-ZrO 2 (x = 0, 3, 5, 7 wt%) were prepared by wet impregnation method and then were tested for syngas production via dry reforming of methane. The reaction temperature at 800 °C was found more catalytically active than that at 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…A deep literature report on a series of the catalyst system in terms of CH 4 conversion, CO 2 conversion, H 2 /CO ratio on different reaction conditions is shown in Table 12,15,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47 . Potassium (K) promotional addition was marked for increasing the mesoporosity and reducibility of the catalyst, 41 Na addition for raising the basicity as well as the formation of strong interacting Ni species (NiO x H y ), 42 Ba addition for the formation of barium zirconate which stabilizes the NiO x species strongly over the surface against agglomeration 43 and Mg addition for increasing the basicity as well as reducible NiO‐MgO solid solution in favour of DRM 48 44 Al and Mn (1:1) had optimized Ni size, high basicity and high adsorbed oxygen species 45 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deep literature report on a series of the catalyst system in terms of CH 4 conversion, CO 2 conversion, H 2 /CO ratio on different reaction conditions is shown in Table 12,15,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47 . Potassium (K) promotional addition was marked for increasing the mesoporosity and reducibility of the catalyst, 41 Na addition for raising the basicity as well as the formation of strong interacting Ni species (NiO x H y ), 42 Ba addition for the formation of barium zirconate which stabilizes the NiO x species strongly over the surface against agglomeration 43 and Mg addition for increasing the basicity as well as reducible NiO‐MgO solid solution in favour of DRM 48 44 Al and Mn (1:1) had optimized Ni size, high basicity and high adsorbed oxygen species 45 .…”
Section: Introductionmentioning
confidence: 99%
“…12,15,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47 Potassium (K) promotional addition was marked for increasing the mesoporosity and reducibility of the catalyst, 41 Na addition for raising the basicity as well as the formation of strong interacting Ni species (NiO x H y ), 42 Ba addition for the formation of barium zirconate which stabilizes the NiO x species strongly over the surface against agglomeration 43 and Mg addition for increasing the basicity as well as reducible NiO-MgO solid solution in favour of DRM. 48 Mg-Al (4:1) promoter brought dispersed small size NiO, strong metal-support interaction, high reducibility and high surface area, 44 Al and Mn (1:1) had optimized Ni size, high basicity and high adsorbed oxygen species. 45 Chromium was found to enhance CO 2 absorption over the surface.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Furthermore, the addition of a promoter over supported Ni catalysts had brought about major physiochemical changes over the catalyst surface in favor of DRM. In brief, Mg incorporation added alkalinity to the catalyst system, 2 , 14 17 Sr boosted Lewis basicity, 18 Yb brought about a high edge of reducibilty, 19 Sc induced basicity and a metal–support interaction, 20 W stabilized the NiO phase and modified the redox behavior, 8 , 21 , 22 Ce or Y advanced lattice ion mobility together with reducibility, 23 − 39 and B or La induced carbon gasification (through B–OH species and La 2 O 2 CO 3 formation, respectively). 40 − 46 Likewise, the addition of Sm, Gd, or Mn–Al (equal proportions) optimized the Ni size and enhanced the metal–support interaction.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the dry reforming of methane (DRM) is a potential and viable option because it yields hydrogen from the conversion of two major greenhouse gases (i.e., CH 4 and CO 2 ). Catalysts based on noble metals have been reported to be effective for DRM. The total methane dissociation energy among the transition metals was found to follow the order Ni < Pd = Pt, so the experimental order of methane conversion was observed to be Ni > Pd = Pt . Among Ni and Co, Gallego et al found that the electronic configuration of Ni in Ni–CH 4 is s 0.54 d 9.42 (with respect to the d 8 s 2 electronic configuration of metallic Ni), indicating smaller steric repulsion between a closed shell of Ni and CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…They found that the potent interaction of NiO-MgO solid solution with the ZrO2 support was essential for obtaining high conversions of both methane and carbon dioxide. Furthermore, over their mixture of metal oxides, carbon dioxide functioned as a soft oxidizing for surface coke, entailing the stability of catalytic performance [16]. Karam et al found the optimum loading of MgO was in the range of 5-10 wt.…”
Section: Introductionmentioning
confidence: 99%